NAMES OF FRUITS IN THE MIDDLE BUG AREA DIALECTS - Поліщук, Світлана (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
Preservation and study of dialect vocabulary, that is a source of national language, are the most important tasks of modern dialectology. Agricultural vocabulary as an integral part of every farmer’s vocabulary is valuable material for dialectological researches. The fixation and analysis of the agricultural lexis in the dialects of the Middle Bug area continues to solve the actual problem of modern linguistics. The purpose of the article is vocabulary-semantic analysis of the lexemes to define names of five fruit trees: cherry, wild cherry, mulberry, apricot and plum, also their fruits and sorts in the Middle Bug area dialects that function at the border of the South-Western and South-Eastern dialects of the Ukrainian language. Methods. During the research, general scientific methods of analysis, synthesis, observation and descriptive method were applied. Among the special linguistic methods involved questionnaires, interviews and lingvo-geographic methods. Results and Discussion. The author’s records and notes done in 74 settlements situated in the west of Kirovohrad region, the northwest of Mykolaiv region, the northeast of Odesa region and the southeast of Vinnytsia region during 2013–2015 are the source of the practical material. The numbering of the villages, urban settlements and towns is used in the article. The full names are listed at the end of the work under the title "The list of the examined settlements and their numbering" to represent the areal distribution of the analyzed dialect units. The examined names and the dialect speech examples are represented by means of the common phonetic transcription for recording the Ukrainian literary and dialect speech (the transcription is presented in the first volume of the Atlas of the Ukrainian Language). The names widespread in Middle Bug area dialects are analyzed. Originality. The article expands the empirical base of Ukrainian dialectology, complements the characterization of the Eastern Podilian dialects of the Podillya dialect of the South-western group and the Western Steppe dialects of the Steppe dialect of the South-eastern group of the Ukrainian language. The conclusion is that the fixed names are connected with literary equivalents although they differ in phonetics, vocabulary and semantics. The work makes it possible to find out how the general dialect vocabulary functions in some dialect groups and dialects. Prospects for further research are the continuation of the study of the Ukrainian dialects of the Middle Bug on the material of fruit names